A51 COMPARISON OF THE BOSTON BOWEL PREPARATION SCALE WITH AN AUDITABLE APPLICATION OF THE US MULTI-SOCIETY TASK FORCE GUIDELINES. (1st March 2018) - Heron, V; Martel, M; Bessissow, T; Chen, Y; Desilets, E; Dube, C; Lu, Y; Ménard, C; McNabb-Baltar, J; Parmar, R; Rostom, A; Barkun, A N
Abstract: Background: Existing bowel preparation scales (BPS) are limited in their ability to predict interval to next colonoscopy. The US Multi-Society Task Force (MSTF) recommends screening or surveillance colonoscopies be repeated within the year if the preparation does not allow for detection of polyps greater than 5 mm in size. Aims: To assess reliability and validity of an auditable application of the MSTF in comparison with the Boston BPS (BBPS). Methods: We developed an auditable application of the MSTF guidelines which we termed the Montreal Bowel Preparation Scale (MBPS). We compared this with the BBPS using a total cut-off score of 6 with each segment score ≥2 (BBPS 2–6). In sensitivity analyses, we applied the MBPS using a cut-off of 3mm rather than 5mm, and also assessed the BBPS using an adequacy threshold of total score ≥5 (BBPS 5). Video recordings of 83 colonoscopies (8 for intra-rater agreements) were independently evaluated by nine physicians trained to use the different scales. Weighted kappas quantified intra- and inter-rater agreements. Intra class correlations were used to assess agreement of the BBPS as a continuous scale. Associations between scores and clinical outcomes were assessed. Results: The BBPS 2–6 and 5mm MBPS showed moderate to substantial intra-rater agreements (κ=0.44–0.63 and κ=0.50–0.53, respectively), while inter-rater agreements were only fair to moderate and slight to moderate (κ=0.25–0.48 and κ=0.19–0.50, respectively). Similar results were noted using alternate thresholds of BBPS 5 and 3mm MBPS. No significant associations were found between scores and clinical outcomes. Conclusions: For all scales, intra-rater kappas were superior to inter-rater values with the latter reflecting at best moderate agreement. This modest performance may reflect the dichotomized interpretation of the scales (adequate vs inadequate) contrary to previous studies which compared scores assessed as continuous variables. Further validation studies of existing ordinal bowel preparation scales should aim to assess reliability in a categorical manner based on proposed adequacy thresholds in order to determine optimal interpretation with regards to interval to next colonoscopy. Funding Agencies: None